Formation and evolution of beach cusps - Sriariyawat, Anurak (2010)
Beach cusps are swash zone morphological patterns that have been of interest to many scientists and engineers. This study aims to improve understanding of the formation and long-term evolution of beach cusps by numerical simulation using a 2D process-based morphodynamic model, solving the coupled NLSW equations and sediment conservation equation simultaneously. A numerical implementation is applied building on the model of Dodd et al. (2008), which succeeds in simulating the occurrence of beach cusps. The numerical scheme improves the accuracy and stability of the swash zone computation. Results from a comparison between different numerical implementations concludes that the most suitable numerical scheme is the Roe-averaged scheme of Castro Diaz et al. (2008) with Minmod flux-limiter using the Harten and Hyman (1983) entropy fix method and the Hubbard and Dodd (2002) approach for the shoreline boundary condition.